Hydrogen bond analysis of the EGFR-ErbB3 heterodimer related to non-small cell lung cancer and drug resistance. (7th March 2019) - Ghosh, Avirup; Yan, Hong
Highlights: In the wild type of that dimer, the hydrogen bonds show more stability. When the dimer becomes mutated (L858R), a few hydrogen bond becomes weak and it breaks with time, so the overall system becomes less stable compare to the wild type stage. Furthermore, when that mutated dimer becomes drug resistive (L858R_T790M), the hydrogen bonds become even more weaker, which results more unstable structure. 3D structures of a protein for rational drug design for conducting mutagenesis research. The need of enhancing the stability of EGFR-drug complex to overcome drug resistance. Abstract: Lung cancer is the predominant cause of cancer deaths on a worldwide scale. A mutation in the epidermal growth factor receptor (EGFR) can cause non-small cell lung cancer (NSCLC). The L858R one-point mutation in exon 21 in EGFR is the most prevalent in NSCLC. For over 60% of EGFR-muted NSCLC, another mutation T790M can cause drug resistance. In this paper, we consider EGFR and ErbB3 heterodimers involving three structures of EGFR, wild-type, with L858R mutation, and with L858R and T790M mutations. We perform molecular dynamics (MD) simulations to analyze hydrogen bonds in all three instances. The hydrogen bonds contribute to the conformational stability of the protein and molecular recognition. Several other parameters are also investigated in the present study, which reveals significant changes in the dimer at different levels of mutation. The knowledge and results obtained from this study lead to useful insight into the mechanism of NSCLC drug resistance.